The Dramatic Structure of Pati in The Story of Babad Pati The Series of Yuyu Rumpung Wahyu Manggolo Studio Pati. - Yunitasari, Tri (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2018)
The story of Babad Pati the series of Yuyu Rumpung is one of the plays often performed by ketoprak studio in Pati. This study aims to find out how the dramatic structure contained in the staging of ketoprak plays the story of Babad Pati the series of Yuyu Rumpung, includes: plot, character, character, background, conversation, theme and mandate covered by the elements of dramatic structure builder. The research method used is using heuristic and hermeneutic reading techniques. The approach used in this research is the objective approach. Objects in this research in story of Babad Pati the series of Yuyu Rumpung by Wahyu Manggolo studio Pati. The data analysis technique used is semiotic structuralism analysis. With the analysis that has been done can be obtained results, among others, the dramatic ladder determinants are divided into six stages consisting of expositipon, complications, conflicts, crises, resolutions and decisions. There are characters, backgrounds and conversations that are elements of story builders. Results of the level of choice of words and sentences that are dominant of Pati dialect. From this research can be an example that dramatic structure is a matter of consideration to build a staging so interesting to watch and contained messages can be delivered properly. The results of this study can be used as one of the other research considerations in other studies, especially the dramatic structure research. Keywords: The Dramatic Structure, Yuyu Rumpung, Babad Pati.